PENINGKATAN MOTORIK HALUS ANAK USIA 4-6 TAHUN MELALUI BERMAIN PLASTISIN DI KOBER TERPADU ST PAULUS KOTAKADHE - Tea, Adolfina; laksana, Dek Ngura Laba; Dua Dhiu, Konstantinus; Ngura, Elisabeth Tantiana (Jurnal Citra Pendidikan, 2025)
Abstract This study aims to improve the fine motor skills of children aged 4-6 years through plasticine play activities at the Integrated Kober ST Paulus Kotakadhe. The method used is class action research (PTK) which consists of two cycles, each of which includes the stages of planning, implementation, observation, and reflection. The results of the study showed that there was an improvement in children's fine motor skills after being given an intervention in the form of playing plasticine. In the first cycle, as many as 30% of children were in the category of Starting to Develop (MB), 50% of children Developing as Expected (BSH), and 20% of Children Developing Very Well (BSB). In cycle II, there was an increase of 10% of children in the category of Starting to Develop (MB), 60% of Children Developing According to Expectations (BSH), and 30% of Children Developing Very Well (BSB). These results show that playing plasticine has a positive impact on improving fine motor skills in early childhood. Thus, the use of plasticine media in learning can be used as an alternative strategy to develop children's fine motor skills. Therefore, it is recommended to educators to further optimize the use of play media that is interesting and in accordance with the stages of children's development.